A good beginning: study protocol for a group-randomized trial to investigate the effects of sit-to-stand desks on academic performance and sedentary time in primary education - A. (Lex); Guido P. H. Band; Joris P. J. Slaets (BMC, 2020)
Abstract Background Sedentary behavior is associated with health risks and academic under-achievement in children. Still, children spend a large part of their waking hours sitting at a desk at school. Recent short-term studies demonstrated the potential of sit-to-stand desks to reduce sitting time in primary education. The program of "A Good Beginning" was conceived to assess the long-term effects of sit-to-stand desks on sitting time in primary education, and to examine how sit-to-stand desks versus regular desks relate to academic performance, and measures of executive functioning, health and wellbeing. The present paper describes the design of this group-randomized trial, which started in 2017 and will be completed in 2019. Methods Children of two grade-three groups (age 8-9) following regular primary education in Leiden, The Netherlands, were recruited. A coin toss determined which group is the experimental group; the other group is the control group. All children in the experimental group received sit-to-stand desks. They are invited and motivated to reduce sedentary time at school, however, it is their own choice to sit or stand. Children in the control group use regular desks. Otherwise, both groups receive regular treatment. Outcomes are assessed at baseline (T0) and at five follow-up sessions (T1-T5) alternately in winter and summer seasons over three academic years. Primary outcome measures are academic performance, and the proportion of sitting time at school, measured with a 3D accelerometer. Secondary outcome measures are a number of measures related to executive functioning (e.g., N-back task for working memory), health (e.g., height and weight for BMI), and wellbeing (e.g., KIDSCREEN-52 for Quality of Life). Discussion A Good Beginning is a two-and-a-half-year research program, which aims to provide a better understanding of the long-term effects of sit-to-stand desks on sedentary time at school and the relation between sitting time reduction and academic performance, executive functioning, health and wellbeing. The findings may serve as useful information for policy making and practical decision making for school and classroom environments. Trial registration The program of "A Good Beginning" is registered at the Netherlands Trial Register (NTR, https://www.trialregister.nl), number NL6166, registration date 24 November 2016.